Influence of bariatric surgery on dental implant treatment (Research, Society and Development, 2022)
Obesity affects the body and makes it conducive to the onset of diabetes, high blood pressure and even potentiate periodontal or peri-implant inflammation. In this scenario, as conventional treatments, there is food change, physical exercise, medication and among other forms. If a favorable result is not obtained, bariatric surgery is recommended to help with weight reduction, with the Roux-en-Y gastric bypass technique being more used. After gastroplasty, nutritional deficiency can occur that can impact bone, dental, periodontal and salivary structure. The main objective of the literature review was to verify whether the nutritional deficit in a patient undergoing bariatric surgery can affect treatment with dental implants. The search was carried out on the Scielo, Google Scholar and PubMed platforms, in Portuguese and English, between 2010 and 2021, with the keywords: “bariatric surgery”, “dental implant”, “nutritional deficiencies” and “obesity” and their English language versions. In total, 28 publications were obtained, 13 of which were selected based on the inclusion criteria. Studies show an association of gastroplasty with dental erosion, caries, periodontal diseases, dry mouth and nutritional deficiencies, especially calcium and vitamin D, which are associated with osteoporosis and secondary hyperparathyroidism and can negatively affect the metabolism and bone structure and treatment with dental implants due to bone loss due to the greater action of osteoclasts and the possibility of peri-implant inflammation. However, there is insufficient scientific evidence to affirm that the nutritional deficiency caused by gastroplasty is able to reduce the potential for osseointegration or the longevity of the implants. Further studies are needed to clarify this relationship.